1998
DOI: 10.1073/pnas.95.15.8886
|View full text |Cite
|
Sign up to set email alerts
|

Dual effect of interleukin 4 on HIV-1 expression: Implications for viral phenotypic switch and disease progression

Abstract: We report that interleukin 4 (IL-4) inhibits the propagation of non-syncytia-inducing and increases the propagation of syncytia-inducing HIV-1 isolates by two mechanisms. It differentially regulates the two major HIV-1 coreceptors, CCR5 and CXCR4, in human peripheral blood mononuclear cells, increasing CXCR4 and decreasing CCR5 expression in primary CD4(+) T-lymphocytes. In addition, IL-4 stimulates the expression of all HIV-1 isolates via a transcriptional activation mechanism. The combination of these effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(111 citation statements)
references
References 46 publications
(40 reference statements)
8
102
0
1
Order By: Relevance
“…6). CXCR4 expression was significantly up-regulated in the presence of IL-4, and there was also a moderate increase in response to IL-2 or IL-15, in accordance with previous reports (35)(36)(37).…”
Section: Figuresupporting
confidence: 92%
See 1 more Smart Citation
“…6). CXCR4 expression was significantly up-regulated in the presence of IL-4, and there was also a moderate increase in response to IL-2 or IL-15, in accordance with previous reports (35)(36)(37).…”
Section: Figuresupporting
confidence: 92%
“…More recently, IL-15 has been shown to have similar effects on some of the CC chemokine receptors (27,33). In contrast, CXCR4 expression is dramatically up-regulated in the presence of IL-4 (35)(36)(37). We have shown that Bonzo, similar to CC chemokine receptors, is induced through stimulation of highly purified resting T cells with IL-2 or IL-15 and is coexpressed with CCR5 or CCR6.…”
Section: Discussionmentioning
confidence: 92%
“…The cytokine environment may determine susceptibility to HIV infection in part by the regulation of HIV-1 coreceptor expression (32). IL-4 down-regulates CCR5 but up-regulates CXCR4 expression on CD4 ϩ T cells and favors high replication of X4 HIV-1 strains (33). IL-4 can also increase HIV-1 replication in DC:T cell cocultures by stimulating T cell proliferation (34).…”
Section: Opposite Effects Of Il-10 On the Ability Of Dendritic Cells mentioning
confidence: 99%
“…In addition, CXCR4 has been identified as a cofactor for HIV entry into T cells (4). We and others have shown previously that cell-surface expression of CXCR4 on T lymphocytes is strongly up-regulated by IL-4, rendering these cells susceptible to infection with certain strains of HIV-1 (5,6). In contrast, T cellexpressed CXCR4 is strongly down-regulated, following TCR/ CD3 complex-mediated activation, using either anti-CD3 mAbs (5,7) or specific Ag (8).…”
mentioning
confidence: 99%